2013
DOI: 10.1021/jp312510d
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Defects in the Local Reaction Kinetics of CO Oxidation on Low-Index Pd Surfaces

Abstract: The role of artificially created defects and steps in the local reaction kinetics of CO oxidation on the individual domains of a polycrystalline Pd foil was studied by photoemission electron microscopy (PEEM), mass spectroscopy (MS), and scanning tunneling microscopy (STM). The defects and steps were created by STM-controlled Ar+ sputtering and the novel PEEM-based approach allowed the simultaneous determination of local kinetic phase transitions on differently oriented μm-sized grains of a polycrystalline sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(59 citation statements)
references
References 53 publications
(104 reference statements)
4
53
1
1
Order By: Relevance
“…sputtered surfaces performed in our recent study showed that ion bombardment of the Pd surface leads to formation of three-dimensional islands, with a very high density of steps and edges [13]. The formed ''mound''-like islands have uppermost terraces with the diameters of 2-3 nm, and the slope angles are between 10°and 20°, corresponding to terrace widths of 0.6-1.2 nm.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…sputtered surfaces performed in our recent study showed that ion bombardment of the Pd surface leads to formation of three-dimensional islands, with a very high density of steps and edges [13]. The formed ''mound''-like islands have uppermost terraces with the diameters of 2-3 nm, and the slope angles are between 10°and 20°, corresponding to terrace widths of 0.6-1.2 nm.…”
Section: Resultsmentioning
confidence: 90%
“…ion bombardement, i.e. with an artificially defected surface [13]. The comparison shows that the reactive behaviour of the Pd agglomerates differs significantly from that of the smooth ordered Pd(111) domain, with the CO poisoning (upper boundary of the bistability region) occurring for Pd powder at a considerably higher CO partial pressure than for the smooth Pt(111) surface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the step density is known to influence the catalytic behaviour, a Rh sample with a step density which is closer to that of the tip surface was prepared by Ar + sputtering of the present Rh foil (cf. our recent STM observation of the Ar + created steps and defects on Pd [34]). The corresponding phase diagram for such an artificially defected Rh surface is also included in Fig.…”
Section: Peem Studiesmentioning
confidence: 80%
“…The ROI for which the PEEM intensity was registered, is marked in (a); c τ A and τ B values for different temperatures in the range of 433-493 K and constant oxygen pressure of 7.7 × 10 −7 mbar, plotted in the p H2 vs 1/T coordinates (kinetic phase diagram). Regions of high and low catalytic activity and of bistability are marked partially filled with sputtered Pd, the reaction fronts were able to cross the grain boundaries [34].…”
Section: Peem Studiesmentioning
confidence: 99%